A PRELIMINARY STUDY ON RADON CONCENTRATIONS AND HEALTH RISK ASSESSMENT OF DRINKING WATER SAMPLES IN KILIS PROVINCE, TURKEY - Canbazoglu, Cumhur; Gundogan, Ayse; Bal, Sultan Sahin; Dogru, Mahmut (Parlar Scientific Publications (P S P), 2020)
Determination of radon concentration in drinking water is very important to assessment whether it poses a health risk in terms of public health or not. For this purpose, radon (Rn-222) concentration of forty nine drinking water samples collected from Kilis province were determined by using CR-39 passive nuclear track detectors with closed-can technique in this study. The radon concentrations for drinking water samples were found between 0.69 and 6.93 Bq L-1 with average of 1.86 Bq All obtained values for radon concentrations were below 11.1 Bq L-1 that recommended as maximum contaminant level (MCL) by the United States Environmental Protection Agency (USEPA). In addition, effective dose and population weighted fatal cancer risk due to Rn-222 in drinking waters were estimated. Average effective dose values were calculated to be 4.75 mu Sv y(-1), 4.69 mu Sv y(-1), 0.57 mu Sv y(-1) and 0.56 mu Sv y(-1) for ingestion, inhalation, stomach and lungs, respectively. All obtained effective dose values were well below the reference level that suggested as 0.1 mSv y(-1) by Word Health Organization (WHO). Population weighted fatal cancer risk varied from 2.62E-06 to 2.54E-04 and average value was found to be 3.07E-05 for Kilis province. In addition, per caput risk was estimated 1.99E-08 due to radon in drinking water samples. Investigated water samples for Kilis province were well below the permissible limits and have no risk to public health.
Keywords: Radon; Drinking water; Annual effective dose; Cancer risk; Nuclear track detectors; Closed-can technique; Kilis